Multiple replication origins with diverse control mechanisms in Haloarcula hispanica. Issue 4 (22nd November 2013) - Wu, Zhenfang; Liu, Jingfang; Yang, Haibo; Liu, Hailong; Xiang, Hua
Abstract: The use of multiple replication origins in archaea is not well understood. In particular, little is known about their specific control mechanisms. Here, we investigated the active replication origins in the three replicons of a halophilic archaeon, Haloarcula hispanica, by extensive gene deletion, DNA mutation and genome-wide marker frequency analyses. We revealed that individual origins are specifically dependent on their co-located cdc6 genes, and a single active origin/ cdc6 pairing is essential and sufficient for each replicon. Notably, we demonstrated that the activities of oriC1 and oriC2, the two origins on the main chromosome, are differently controlled. A G-rich inverted repeat located in the internal region between the two inverted origin recognition boxes (ORBs) plays as an enhancer for oriC1, whereas the replication initiation at oriC2 is negatively regulated by an ORB-rich region located downstream of oriC2-cdc6E, likely via Cdc6E-titrating. The oriC2 placed on a plasmid is incompatible with the wild-type (but not the Δ oriC2 ) host strain, further indicating that strict control of the oriC2 activity is important for the cell. This is the first report revealing diverse control mechanisms of origins in haloarchaea, which has provided novel insights into the use and coordination of multiple replication origins in the domain of Archaea.